Factors that influence small-scale Fishers' readiness to exit a declining fishery in Davao Gulf, Philippines. (1st November 2022) - Macusi, Edison D.; Liguez, Chency Grace O.; Macusi, Erna S.; Liguez, Arianne Kay O.; Digal, Larry N.
Abstract: Excessive fishing pressure and overexploitation in the fishing grounds are common reasons of catch decline. This study assessed the small-scale fisheries in Davao Gulf regarding their dwindling catch by examining their motivations to exit the fisheries when presented with cash incentives. Given the catch declines experienced by fishers, it is vital to address and determine which socioeconomic and fisheries factors influence their exit behavior. The study used a semi-structured survey questionnaire to collect socioeconomic and fisheries data using face-to-face interviews in landing sites and fishers' homes. Fishers were asked regarding their exit from the fisheries in various study sites: Governor Generoso, Lupon, Davao City, Sta. Maria, Don Marcelino, and Malita (N = 229). The results showed that most fishers would not exit from the fisheries unless they were given a monthly subsidy of Php 15, 000 (∼289 U$). More than 75% of the fishers were willing to leave the fisheries if given Php 15, 000 as a cash subsidy. Fishers considered both fisheries and economic factors in their decision to exit. Further analysis showed that the fishers' revenue was primarily affected by the number of fishing trips, fish price, and fishing costs which significantly impacted their operations (df = 10, MS = 0.67, F  = 4.95, p  = .001). The results show a strong economic motivation for fishers ready to exit from the fisheries. It supports the need for livelihood diversification, skills upgrading, financial grants and assistance for those who want to exit the fisheries to reduce fishing effort and sustainably manage the fisheries.